2008
DOI: 10.1038/nature07179
|View full text |Cite
|
Sign up to set email alerts
|

CDK8 is a colorectal cancer oncogene that regulates β-catenin activity

Abstract: Aberrant activation of the canonical Wnt/β-catenin pathway occurs in almost all colorectal cancers and contributes to their growth, invasion and survival. Although dysregulated β-catenin activity drives colon tumorigenesis, additional genetic perturbations are required to elaborate fully malignant disease. To identify genes that both modulate β-catenin activity and are essential for colon cancer cell proliferation, we conducted two loss-of-function screens in human colon cancer cells and compared genes identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
685
8
5

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 614 publications
(726 citation statements)
references
References 30 publications
28
685
8
5
Order By: Relevance
“…Keywords: cyclin-dependent kinae 8 (CDK8), endometrial cancer, tumorigenesis, cell growth, cell migration identified as an oncoprotein, 6,7 yet the underlying mechanisms of how elevated CDK8 promotes tumorigenesis remain unclear. Second, because CDK8 is a kinase, there is considerable interest in developing cancer drugs by targeting CDK8.…”
Section: Tumor-suppressive Effects Of Cdk8 In Endometrial Cancer Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Keywords: cyclin-dependent kinae 8 (CDK8), endometrial cancer, tumorigenesis, cell growth, cell migration identified as an oncoprotein, 6,7 yet the underlying mechanisms of how elevated CDK8 promotes tumorigenesis remain unclear. Second, because CDK8 is a kinase, there is considerable interest in developing cancer drugs by targeting CDK8.…”
Section: Tumor-suppressive Effects Of Cdk8 In Endometrial Cancer Cellsmentioning
confidence: 99%
“…Thus to further examine the notion that CDK8 inhibits the growth of endometrial cancer cells, we depleted CDK8 in AN3 CA cells by transducing the cells with pLKO.1-shRNAs, which were previously shown to specifically target CDK8. 6,7,31,36,38 Similar construct targeting GFP (sh-GFP) was used as the negative control. Transduced cells were selected by puromycin for over 2 wk, and the efficiency of CDK8 knockdown was verified by qRT-PCR and western blot.…”
Section: Tumor-suppressive Effects Of Cdk8 In Endometrial Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the carcinomas several other regions on several chromosomes including 1, 3 and 10 were found to be significantly associated with chr16p-loss. To reduce the possibility that the associations identified were false positives, an independent sample set consisting of 128 colorectal carcinomas, copy-number profiled by 250K Sty SNP arrays in a recent study, 15 was also analyzed. In accordance with our study, we also found chr16p-loss to be a frequent alteration, 41% (52/128), in this sample set and comparison of the alterations associated with chr16p-loss in this set and our carcinoma set pointed to only a single CNA, loss of a region at chr3p22.3 (34.3-36.3 Mb).…”
Section: Specific Copy-number Alterations Co-occur With Chr16p-lossmentioning
confidence: 99%
“…Genomic analyses of cancer samples, by cytogenetic studies and more recently by array-based profiling, have identified recurrent alterations associated with all investigated cancer types. [7][8][9][10][11] With respect to CRC, a few CNAs have been associated with outcome, [12][13][14] some have led to the identification of cancercausing genes, 15 and others have suggested potential therapeutic strategies. 16 Over the recent years, advances in genome characterization technologies have enabled increasingly systematic efforts to characterize genomic alterations in human cancer samples.…”
mentioning
confidence: 99%